PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN - Edwin Faisal Saputra; Meilaty Finthariasari; Taufik Bustami (UM. Bengkulu, 2020)
This study aims to determine the effect of Work Environment and Organizational Culture on Employee Productivity at PT. Agro Muko RMO Mukomuko. This research is a quantitative study with a population of 46 employees in the palm oil production division. The sampling technique of this study was to use saturated sampling in which a total population was sampled as many as 46 employees. Data collection method using a questionnaire. The data analysis technique used is the assumption test, multiple linear regression, coefficient of determination, and hypothesis testing. Based on the results of the research hypothesis test shows that the Work Environment and Organizational Culture simultaneously have a significant effect on work productivity at PT. Agro Muko RMO Mukomuko where the calculated F value (9.833)> F table (3.21). While partially Work Environment variables significantly influence Work Productivity where the value of t arithmetic (2,664)> t table (2,014) and Organizational Culture variables significantly influence Work Productivity with t arithmetic (2,454)> t table (2,014). The results of the coefficient of determination of R Square is equal to 0.314. This means that Work Productivity can be influenced by 31.4% by the independent variable Work Environment and Organizational Culture. While the rest (100% - 31.4% = 68.6%) is influenced by other variables not examined in this study. Keywords: Work Environment, Organizational Culture and Work Productivity.